MOLECULAR AND MORPHOLOGICAL IDENTIFICATION OF STREPTOMYCES SP. NRC-88 NOVA SPECIES AS Î²-LACTAMASE INHIBITOR FOR PHARMACEUTICAL APPLICATION - Mohamed Awad, Hassan; Germoush, Mousa O (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: Clavulanic acid (CA) is a vital agent in the treatment of bacterial infections since it is a potent inhibitor of an extensive variety of Î²-lactamase enzymes. Its production from Streptomyces strains is fact of expanding clinical significance. This study aimed to isolate and characterize a promising Streptomyces (S) species strain which produced an effective Î²-lactamase inhibitor. Methods: Streptomyces sp. NRC-88 was isolated from an Egyptian soil sample. The phenotypic and phylogenetic examinations of 16S rRNA gene were investigated. The active metabolite of this strain (CA) was determined by particular synergistic bioassay, spectrophotometric assay, recognized by thin layer chromatography, and structure of the CA affirmed by high-performance liquid chromatography (HPLC) method. Results: A phylogenetic examination of the 16S rRNA gene sequence of the NRC-88 strain consistent with conventional taxonomy was carried out, and confirmed that the strain NRC-88 was most similar to S. aburaviensis S-66 (99%). The active metabolite of this strain (CA) was determined by different methods and confirmed the structure of the CA by the HPLC method. It produced up to 87 mg/l in a specific CA production medium. Conclusion: A new species of Streptomyces sp. NRC-88 isolated and recognized by phenotypic and genotypic proof. This strain suggested the name, Streptomyces sp. NRC-88 (accession number KM014489). It was able to produce CA as the Î²-lactamase inhibitor.